Navigation-Assisted Nasal Bone Osteotomy for Malunited Fracture. Issue 1 (January 2018) - Ogino, Akihiro; Onishi, Kiyoshi; Nakamichi, Miho; Okaneya, Tetsuya
Abstract : Background: Nasal bone osteotomy subjectively judges the position for osteotomy by visual inspection and by manual feel using the fingertip. Therefore, the outcome depends on the surgeon's experience and mastery of the procedure is technically challenging. Methods: The authors applied a navigation system for the intraoperative evaluation of the osteotomy line and reduction position in 5 patients with malunited nasal bone fracture. The authors performed the operation with a temporal bone post developed for otologic surgery using Stealth Station S7 System (Medtronic, Minneapolis, MN). The suretrack is attached to the bone chisel. The authors performed the osteotomies while visualizing the tip of the chisel on the monitor. In addition, evaluation of the reduction position was performed by insertion of a 23G needle syringe with the suretrack to the nasal bone surface. Results: The tip of the bone chisel was visible on the monitor, and the authors could perform osteotomies while confirming the position and direction of osteotomy. In addition, the reduction position could be visualized clearly on the monitor. Conclusion: Navigation systems can confirm the 3-dimensional spatial relationship around the fracture site in real time, requiring only comparatively simple preoperative preparation and intraoperative operation without radiation exposure. Therefore, the advantage is that even an inexperienced surgeon can perform an accurate evaluation. This would be useful as a guide for young doctors and medical students as it would be possible to perform safe and accurate osteotomy for old nasal bone fractures.